2017
DOI: 10.1016/j.jpba.2017.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and validation of a MCC/IMS prototype for exhaled propofol online measurement

Abstract: Propofol is a commonly used intravenous general anesthetic. Multi-capillary column (MCC) coupled Ion-mobility spectrometry (IMS) can be used to quantify exhaled propofol, and thus estimate plasma drug concentration. Here, we present results of the calibration and analytical validation of a MCC/IMS pre-market prototype for propofol quantification in exhaled air. Calibration with a reference gas generator yielded an R≥0.99 with a linear array for the calibration curve from 0 to 20 ppb. The limit of quantificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“… 13 , 35 Kreuer et al calculated a much lower conversion factor of 0.66 ppb/ml/μg, which may be disregarded since they used a calibration procedure not presently recommended. 18 , 36 Chen et al demonstrated interindividual variability in the blood/exhaled partial pressure ratio (R BE ) of propofol and have proposed a method of individualised calculation of this ratio. However, this takes up to 50 min to determine per patient using a gas chromatograph–surface acoustic wave sensor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 , 35 Kreuer et al calculated a much lower conversion factor of 0.66 ppb/ml/μg, which may be disregarded since they used a calibration procedure not presently recommended. 18 , 36 Chen et al demonstrated interindividual variability in the blood/exhaled partial pressure ratio (R BE ) of propofol and have proposed a method of individualised calculation of this ratio. However, this takes up to 50 min to determine per patient using a gas chromatograph–surface acoustic wave sensor.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 Refinement of the IMS technology combined with a multiple capillary column (MCC‐IMS) for handling humid gas has led to the launch of a CE‐marked, bedside, online drug monitor for quantifying propofol concentrations in exhaled air at a rate of once per minute, the Edmon ® (B. Braun Melsungen AG, Germany). 16 , 17 , 18 Obesity alters respiratory physiology, including reduced functional residual capacity with risk of atelectases and ventilation‐perfusion mismatch. 2 Thus, the suitability of MCC‐IMS technology in obese patients is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defined standards of desflurane and sevoflurane ranging from 1 to 7000 ppb (0.001 to 7 ppm) were used for calibration. Limits of detection and limits of quantification were determined as previously described by Maurer et al 13 Limit of detection/quantification was 0.8/0.9 ppb (0.0008/0.0009 ppm) for desflurane, and 2.2/2.4 ppb (0.0022/0.0024 ppm) for sevoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…Several technologies for VOC analysis have emerged in recent decades, allowing for potential non-invasive and rapid discovery of VOC patterns: electronic nose [ 7 , 8 ], gas chromatography-mass spectrometry (GC-MS) [ 9 , 10 ], liquid chromatography-mass spectrometry (LC-MS) [ 11 , 12 ] and multi-capillary-column ion-mobility-spectrometry [ 13 , 14 , 15 ] based devices are used for a majority of trials. MCC-IMS devices have seen an increase in popularity—e.g., in the detection of anesthetics in the workplace [ 16 ], accurate tracking and quantification of gaseous propofol concentration during surgery [ 17 ], identification of VOCs in idiopathic pulmonary fibrosis [ 18 ] and for breast cancer detection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%